Semantic representation of bullying in mexican children of school age - Valencia Ortiz, Andrómeda Ivette (Consorcio de Universidades Mexicanas A.C., 2015)
The progressive increase in bullying in Mexican children demonstrates the need for the most accurate information around this problem. Mexico has generated some strategies care prevention in the bullying problem, however, the evaluation of this phenomenon lies in the main actors (victim, attacker), leaving aside valuable information that can provide the viewers of this phenomenon, useful information for the advancement of the characterization of the bullying phenomenon and the prevention and intervention. Hence the importance of the study under this descriptive approach. This study aimed to know the perception of children from elementary school around bullying; specifically the meanings attributed to the terms “bullying” and “isolation” as stimulus words, besides to know the perception of children (guiding phrases) of the role of the victim, the role of the viewer and perception about teacher ́s supervision in bullying. This was a qualitative, exploratory and descriptive study, using the technique of natural semantic networks. Participants were a group of 208 elementary school children with an age range between 8 and 13 years. The data obtained allowed to classify the stimulus word answers for bullying and isolation in three broad categories: physical violence, verbal violence and psychological-emotional violence. The results and implications of the study were analyzed and discussed.